Hubungan Pola Pemberian Makan dan Riwayat Pemberian ASI Ekslusif Terhadap Kejadian Stunting pada Balita Usia 24 – 59 Bulan di Wilayah Kerja Puskesmas Tempuran Kabupaten Karawang - Tita Ismayanti; Lia Idealistiana (Malahayati Nursing Journal, 2024)
ABSTRACT The growth and development of children is strongly influenced by nutritional status. Inadequate nutrition during the first 1000 days of life can cause growth disturbances, one of which is stunting. stunting has an impact on the level of intelligence, susceptibility to disease, decreased productivity. Exclusive breastfeeding is associated with the incidence of stunting in toddlers, because exclusive breastfeeding can reduce the risk of stunting. To find out whether there is a relationship between feeding patterns and history of exclusive breastfeeding with stunting in toddlers aged 24-59 months in the working area of the Tempuran Health Center, Karawang Regency. The type of research used in this research is quantitative research with a correlative descriptive design and uses a cross-sectional study approach. The population in this study were all mothers who had toddlers aged 24 months - 59 months in the working area of the Tempan Health Center, Karawang district, namely 2,000 toddlers. The sample in this study was adjusted using a simple random sampling technique to be as many as 100 toddlers. The types of data used in this research are primary data and secondary data. The data were then analyzed using univariate analysis of frequency distribution and bivariate chi square test. The results of the statistical test on feeding patterns using the chi-square test obtained a p-value = 0.000 with a significance level of 5% p-value, which means 0.000 0.05. As for the statistical test results for the history of exclusive breastfeeding using the chi-square test, it obtained a value of p = 0.004, which means p - value 0.05 (0.004 0.05). There is a significant relationship between feeding patterns and history of exclusive breastfeeding with the incidence of stunting in toddlers aged 24-59 months in the Work Area of the Karawang District Health Center. Keywords: Diet, Exclusive Breastfeeding, Stunting  ABSTRAK Pertumbuhan dan perkembangan anak sangat dipengaruhi oleh status gizi. Tidak terpenuhinya gizi selama periode 1000 hari pertama kehidupan dapat menyebabkan gangguan pertumbuhan, salah satu gangguan pertumbuhan tersebut adalah stunting. stunting berdampak pada tingkat kecerdasan, kerentanan terhadap penyakit, menurunnya produktifitas. ASI ekslusif dikaitkan dengan kejadian stunting pada balita, dikarenakan asi ekslusif dapat mengurangi resiko resiko terjadinya stunting. Untuk mengetahui apakah ada Hubungan Pola Pemberian Makan Dan Riwayat Pemberian ASI Ekslusif Dengan Kejadian Stunting Pada Balita Usia 24 - 59 Bulan di Wilayah Kerja Puskesmas Tempuran Kabupaten Karawang. Jenis penelitian yang digunakan dalam penelitian ini adalah penelitian kuantitatif dengan desain deskriptif korelatif dan menggunakan pendekatan cross-sectional study. Populasi pada penelitian ini adalah seluruh ibu yang memiliki balita usia 24 bulan - 59 bulan di wilayah kerja puskesmas tempuran kabupaten karawang yaitu sebanyak 2000 balita. Sampel dalam penelitian ini di sesuaikan menggunakan teknik simple random sampling menjadi sebanyak 100 balita. Jenis data yang digunakan dalam penelitian ini adalah data primer dan data sekunder. Data kemudian dianalisis menggunakan analisis univariat distribusi frekuensi dan bivariat uji chi square. Hasil uji statistic pola pemberian makan menggunakan uji chi square di dapatkan nilai p value = 0,000 dengan taraf signifikasi 5% p – value yang berarti 0,000 0,05. Adapun hasil uji statistik riwayat pemberian ASI ekslusif menggunakan uji chi-square didapatkan nilai p = 0,004 yang berarti p – value 0,05 (0,004 0,05). Ada hubungan yang signifikan antara pola pemberian makan dan riwayat pemberian ASI ekslusif dengan kejadian stunting pada balita usia 24 – 59 bulan di Wilayah Kerja Puskesmas Kabupaten Karawang. Kata Kunci: Pola makan, ASI Ekslusif, Stunting